ZISWAF Digital Payment as An Effort to Reach Millennials - Fuad Hasyim; Muhammad Al-Farido Awwal; Nur Hidayah Al Amin (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2020)
Abstract: ZISWAF is an Islamic-led fundraising instrument aimed at wealth distribution. The existence of technological developments allows the adaptation of payments with all its acceleration. This study aims to determine the digital payment strategy to maximize ZISWAF’s revenue potential in Indonesia. This study uses the TAM, and TPB modification approaches. The methodology used is structural equation modeling (SEM) with a partial least square (PLS) approach. The sample used is the Y generation as a representation of the millennial generation. The results showed that all the variables forming the TAM theory (perceived usefulness, perceived ease of use, attitude) and all the variables creating the TPB theory (subjective norms and perceived behavior control) significantly affect the Intention (INT) of individuals pay for online ZISWAF (sig. 0.05, α=5%). Furthermore, attitude is a mediating variable in a partial/ quasi modification model that links perceived usefulness (PU), perceived ease of use (PEoU) to Intention (INT) (VAF=49.87%).Abstrak: ZISWAF adalah instrumen pengumpulan dana yang dipelopori Islam dengan tujuan untuk distribusi kekayaan. Adanya perkembangan teknologi memungkinkan adaptasi pembayaran dengan segala akselerasinya. Penelitian ini bertujuan untuk mengetahui strategi pembayaran digital untuk memaksimumkan potensi pendapatan ZISWAF di Indonesia. Penelitian ini menggunakan pendekatan modfikasi TAM dan TPB. Metodologi yang digunakan adalah structural equation modeling (SEM) dengan pendekatan partial least square (PLS). Sampel yang digunakan merupakan generasi Y sebagai representasi generasi milenial. Hasil menunjukkan seluruh variabel pembentuk teori TAM yakni perceived usefulness (PU), perceived ease of use (PEoU) dan attitude (ATT) dan seluruh variabel pembentuk teori TPB yakni subjective norms (SN) dan perceived behavior control (PBC) berpengaruh terhadap intention (INT) individu dalam membayar ZISWAF secara online (sig. 0.05, α=5%). Attitude (ATT) merupakan variabel pemediasi dalam model modifikasi yang bersifat partial/ quasy yang menghubungkan perceived usefulness (PU), perceived ease of use (PEoU) terhadap intention (INT) (VAF=49.87%)